Wanprestasi Pihak Debitur dalam Perjanjian Non Kontraktual dengan Jaminan Gadai - Bagus Alit Pradnyana Artha Wirawan; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
Indonesia is a developing country with various kinds of economic development. Bound by government regulations, the community cannot act arbitrarily and must follow applicable norms. The government in an effort to equalize the welfare of its people frees the community to manage their funds or loans with collateral. The purpose of this study is to understand the legal construction of non-contractual debt agreements with collateral and to analyze the legal protection for the parties to non-contractual debt agreements in the event that the debtor defaults. Researchers search for information directly through collecting data from several legal books and linking it to the problems studied and then drawing conclusions, this research is often called a normative research method using a statutory approach. Honesty and obedience in unsecured agreements are based on trust between the parties concerned, especially the lender and the borrower. There are often defaults in this agreement where the borrower does not pay for various reasons but is absent from payment, various problems such as the borrower disappears or runs away, does not feel he has debt, feels unfair with the interest given but is not stated when making the agreement, many borrower incidents do not want to pay because the agreement does not include a letter of agreement and prioritizes trust.